Analisis Paparan Konten Instagram @narasinewsroom Mengenai Partisipasi Publik dalam Penyebaran Tagar #IndonesiaGelap - Anang Rivai, Muhamad; Nurazizah, Siti; Wijayanti, Yani Tri (Universitas Muhammdiyah Yogyakarta, 2026)
This research aims to analyze how exposure to Instagram content tagged #IndonesiaGelap on the @narasinewsroom account shapes public attention and participation in the digital space. The study applies the Agenda Setting theory, which emphasizes the media’s capacity to influence which issues are perceived as important by the public through content intensity, consistency, and prominence. The research employs a quantitative content analysis method on Instagram posts and audience comments by categorizing content themes, message types, and comment sentiments (positive, negative, and neutral). Data are analyzed based on frequency patterns and levels of audience interaction as indicators of the public agenda. The findings reveal that content exposure is predominantly centered on public policy issues, with negative sentiment emerging as the most dominant response among audiences. This dominance reflects heightened public attention and accumulated dissatisfaction with state policies that have become central within Instagram discourse. Overall, the study confirms that exposure to social media content plays an effective role in shaping the public agenda and stimulating digital audience participation.